2021
DOI: 10.1101/2021.04.27.21256193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-world effectiveness of Ad26.COV2.S adenoviral vector vaccine for COVID-19

Abstract: In light of the massive and rapid vaccination campaign against COVID-19, continuous real-world effectiveness and safety assessment of the FDA-authorized vaccines is critical to amplify transparency, build public trust, and ultimately improve overall health outcomes. In this study, we leveraged large-scale longitudinal curation of electronic health records (EHRs) from the multi-state Mayo Clinic health system (MN, AZ, FL, WN, IA). We compared the infection rate of 2,195 individuals who received a single dose of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The continual emergence of SARS-CoV-2 variants with increased transmissibility and capacity for immune escape, such as B.1.1.7 ("UK variant") and P.1 ("Brazilian variant"), threatens to prolong the pandemic through devastating outbreaks such as the one currently being witnessed in India 2 . While multiple vaccines have demonstrated high effectiveness in clinical trials and real world studies [3][4][5] , there have been reports of "vaccine breakthrough infections" with SARS-CoV-2 variants 6,7 . A recent study described two such cases in New York, at least one of which occurred despite confirmation of a robust neutralizing antibody response.…”
Section: Introductionmentioning
confidence: 99%
“…The continual emergence of SARS-CoV-2 variants with increased transmissibility and capacity for immune escape, such as B.1.1.7 ("UK variant") and P.1 ("Brazilian variant"), threatens to prolong the pandemic through devastating outbreaks such as the one currently being witnessed in India 2 . While multiple vaccines have demonstrated high effectiveness in clinical trials and real world studies [3][4][5] , there have been reports of "vaccine breakthrough infections" with SARS-CoV-2 variants 6,7 . A recent study described two such cases in New York, at least one of which occurred despite confirmation of a robust neutralizing antibody response.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported efficacy and effectiveness estimates for the single dose Johnson & Johnson vaccine which informed 5 of the 12 possible estimates 54,55 (Figure 5 and Table 2). We estimated a 66%, 73%, 83%, efficacy for wild-type against any infection, symptomatic disease, and severe disease respectively.…”
Section: Johnson and Johnson (Viral Vector)mentioning
confidence: 99%
“…We estimated a 66%, 73%, 83%, efficacy for wild-type against any infection, symptomatic disease, and severe disease respectively. Five estimates for efficacy against symptomatic disease were identified ranging from 66.9% (95% CI: 59.0, 73.4) 54 to 76.7% (95% CI: 30.3, 95.3) 55 . No data were available for efficacy against transmission, therefore we assumed this to be the same as for AstraZeneca.…”
Section: Johnson and Johnson (Viral Vector)mentioning
confidence: 99%
“…The continual emergence of SARS-CoV-2 variants with increased transmissibility and capacity for immune escape, such as B.1.1.7 ("UK variant") and P.1 ("Brazilian variant"), threatens to prolong the pandemic through devastating outbreaks such as the one currently being witnessed in India 2 . While multiple vaccines have demonstrated high effectiveness in clinical trials and real world studies [3][4][5] , there have been reports of "vaccine breakthrough infections" with SARS-CoV-2 variants 6,7 . A recent study described two such cases in New York, at least one of which occurred despite confirmation of a robust neutralizing antibody response.…”
Section: Introductionmentioning
confidence: 99%